Thermodynamic Evaluation on Alkoxyamines of TEMPO Derivatives, Stable Alkoxyamines or Potential Radical Donors?. Issue 45 (1st December 2022) - Qian, Bao‐Chen; Zhang, Lu; Zhang, Gao‐Shuai; Fu, Yan‐Hua; Zhu, Xiao‐Qing; Shen, Guang‐Bin
Abstract: In this work, the bond dissociation energy (BDE) values, including BDE(O−X) and BDE(N−O), for 129 alkoxyamines (XRT) of TEMPO derivatives were predicted, and the evaluations on stabilities of alkoxyamines, reactivities of alkoxyamines as radical donors and reactivity of TEMPO as various radical scavenger are well compared and discussed based on the predicted BDE values from the view of thermodynamic driving forces. Without a doubt, the wide and valuable BDE values are helpful for chemists better understand the thermodynamic properties and kinetic behaviors of alkoxyamines and TEMPO in chemical reactions and drug metabolism in vivo and promoting the rapid development and application of novel alkoxyamines. Abstract : Since the vital applications of alkoxyamines in NMP, drugs or pro‐drugs, and chemical synthesis are dependent on BDEs of O−X and N−O bonds, the BDEs for 129 alkoxyamines of TEMPO derivatives were predicted, and the evaluations on stabilities of alkoxyamines, reactivities of alkoxyamines as radical donors and reactivity of TEMPO as various radical scavenger are well compared and discussed.